B Cell Numbers Predict Humoral and Cellular Response Upon SARS–CoV‐2 Vaccination Among Patients Treated With Rituximab. Issue 6 (17th April 2022) - Stefanski, Ana‐Luisa; Rincon‐Arevalo, Hector; Schrezenmeier, Eva; Karberg, Kirsten; Szelinski, Franziska; Ritter, Jacob; Jahrsdörfer, Bernd; Schrezenmeier, Hubert; Ludwig, Carolin; Sattler, Arne; Kotsch, Katja; Chen, Yidan; et al.
Abstract : Objective: Patients with autoimmune inflammatory rheumatic diseases receiving rituximab (RTX) therapy are at higher risk of poor COVID‐19 outcomes and show substantially impaired humoral immune response to anti–SARS–CoV‐2 vaccine. However, the complex relationship between antigen‐specific B cells and T cells and the level of B cell repopulation necessary to achieve anti‐vaccine responses remain largely unknown. Methods: Antibody responses to SARS–CoV‐2 vaccines and induction of antigen‐specific B and CD4/CD8 T cell subsets were studied in 19 patients with rheumatoid arthritis (RA) or antineutrophil cytoplasmic antibody–associated vasculitis receiving RTX, 12 patients with RA receiving other therapies, and 30 healthy controls after SARS–CoV‐2 vaccination with either messenger RNA or vector‐based vaccines. Results: A minimum of 10 B cells per microliter (0.4% of lymphocytes) in the peripheral circulation appeared to be required for RTX‐treated patients to mount seroconversion to anti‐S1 IgG upon SARS–CoV‐2 vaccination. RTX‐treated patients who lacked IgG seroconversion showed reduced receptor‐binding domain–positive B cells ( P = 0.0005), a lower frequency of Tfh‐like cells ( P = 0.0481), as well as fewer activated CD4 ( P = 0.0036) and CD8 T cells ( P = 0.0308) compared to RTX‐treated patients who achieved IgG seroconversion. Functionally relevant B cell depletion resulted in impaired interferon‐γ secretion by spike‐specific CD4 T cells ( P = 0.0112, r = 0.5342). In contrast, antigen‐specific CD8 T cells were reduced in both RA patients and RTX‐treated patients, independently of IgG formation. Conclusion: In RTX‐treated patients, a minimum of 10 B cells per microliter in the peripheral circulation is a candidate biomarker for a high likelihood of an appropriate cellular and humoral response after SARS–CoV‐2 vaccination. Mechanistically, the data emphasize the crucial role of costimulatory B cell functions for the proper induction of CD4 responses propagating vaccine‐specific B cell and plasma cell differentiation.